Electrochemical element, its manufacturing method, and electrochemical device

By employing a current collector with an active material layer of lithium silicate composite particles coated with a specific oxide layer, the challenges of capacity retention and corrosion in lithium-ion secondary batteries are addressed, resulting in enhanced durability and performance.

JP7656831B2Active Publication Date: 2025-04-04PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021574528
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-01-31
Filing Date
2020-12-17
Publication Date
2025-04-04
Estimated Expiration
2040-12-17

AI Technical Summary

Technical Problem

Lithium-ion secondary batteries using silicon compounds as negative electrode materials face challenges with capacity retention due to corrosion from side reactions during battery operation, which is more severe than with carbon-based materials.

Method used

The use of a current collector with an active material layer comprising lithium silicate composite particles, where silicon particles are dispersed within the lithium silicate phase and coated with a first coating containing an oxide of a specific element (other than a non-metallic element) that is thicker near the current collector to suppress corrosion, while maintaining electrical conductivity by adjusting the coating thickness and composition.

Benefits of technology

This configuration enhances the capacity retention rate of electrochemical devices by reducing corrosion effects and maintaining electrical conductivity, leading to improved durability and performance of lithium-ion secondary batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007656831000002
    Figure 0007656831000002
  • Figure 0007656831000003
    Figure 0007656831000003
  • Figure 0007656831000004
    Figure 0007656831000004
Patent Text Reader

Abstract

This electrochemical element comprises: a current collector; and an active material layer supported on the current collector, wherein the active material layer includes active material particles. The active material particles include: lithium silicate complex particles containing a lithium silicate phase and silicon particles dispersed in the lithium silicate phase; and a first coating film which covers at least a portion of the lithium silicate complex particles. The first coating film includes an oxide of a first element other than a non-metallic element. When the thickness of the active material layer is TA, the thickness T1b in the active material layer of the first coating film which covers the lithium silicate complex particles located at a position of 0.25TA from the surface of the current collector, and the thickness T1t in the active material layer of the first coating film which covers the lithium silicate complex particles located at a position of 0.75TA from the surface of the current collector satisfy T1b > T1t.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure primarily relates to improvements in active material layers. [Background technology]

[0002] As the applications of electrochemical devices become more diverse, improvements in various performances are being demanded. In this regard, Patent Document 1 proposes coating the surfaces of the positive and negative electrodes with a metal oxide. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2017-97999 A Summary of the Invention

[0004] One of the performance requirements for electrochemical devices is to increase capacity. For example, in lithium-ion secondary batteries, the use of silicon compounds as negative electrode materials has been considered. It is also known that silicon compounds are more susceptible to corrosion due to side reactions during battery operation than carbon materials used as negative electrode materials. Therefore, even when silicon compounds are used as active material particles, it is necessary to suppress the decrease in the capacity retention rate of electrochemical devices.

[0005] One aspect of the present disclosure relates to an electrochemical element comprising: a current collector; and an active material layer supported on the current collector, the active material layer comprising active material particles comprising lithium silicate composite particles including a lithium silicate phase and silicon particles dispersed within the lithium silicate phase; and a first coating covering at least a portion of a surface of the lithium silicate composite particles, the first coating comprising an oxide of a first element other than a non-metallic element, wherein a thickness T1b of the first coating covering the lithium silicate composite particles located at a position 0.25TA from the surface of the current collector in the active material layer and a thickness T1t of the first coating covering the lithium silicate composite particles located at a position 0.75TA from the surface of the current collector in the active material layer satisfy T1b>T1t, where TA is a thickness of the active material layer.

[0006] Another aspect of the present disclosure relates to an electrochemical device comprising a first electrode, a second electrode and a separator interposed therebetween, one of the first electrode and the second electrode being constituted by the above-described electrochemical element.

[0007] Yet another aspect of the present disclosure relates to a method for manufacturing an electrochemical element, comprising: a preparation step of preparing lithium silicate composite particles containing a lithium silicate phase and silicon particles dispersed in the lithium silicate phase; a support step of supporting the lithium silicate composite particles on a surface of a current collector; and, after the support step, a coating formation step of exposing the lithium silicate composite particles to a gas phase containing a first element other than non-metallic elements to form a first coating containing an oxide of the first element on at least a portion of the surface.

[0008] According to the present disclosure, it is possible to increase the capacity retention rate of an electrochemical device. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a schematic cross-sectional view showing a main part of an electrochemical device according to an embodiment of the present disclosure. [Diagram 2]FIG. 2 is a schematic cross-sectional view showing a further enlarged view of a main part of the electrochemical device shown in FIG. [Diagram 3] FIG. 3 is a schematic cross-sectional view showing in detail an active material particle according to an embodiment of the present disclosure. [Figure 4] FIG. 4 is a schematic perspective view, with a portion cut away, of a nonaqueous electrolyte secondary battery according to one embodiment of the present disclosure. [Diagram 5] FIG. 5 is a flowchart showing a method for manufacturing an electrochemical device according to an embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] A. Electrochemical element An electrochemical element according to an embodiment of the present disclosure includes a current collector and an active material layer supported on the current collector. The active material layer includes active material particles. The active material particles include lithium silicate composite particles including a lithium silicate phase and silicon particles dispersed within the lithium silicate phase, and a first coating that covers at least a portion of the surface of the lithium silicate composite particles. The first coating includes an oxide of a first element other than a nonmetallic element.

[0011] The first coating is thicker on active material particles closer to the surface of the current collector. Corrosion of active material particles arranged near the current collector has a large impact on the durability of the electrochemical device. By thickening the coating of the lithium silicate composite particles arranged near the current collector, the effect of suppressing the corrosion is improved. Thus, the durability of the electrochemical device is improved. On the other hand, the first coating of the lithium silicate composite particles located away from the current collector is thin, so that the decrease in the conductivity of the active material particles is suppressed.

[0012] Specifically, when the thickness of the active material layer is TA, the thickness T1b of the first coating covering the lithium silicate composite particles located at a position of 0.25TA from the surface of the current collector of the active material layer and the thickness T1t of the first coating covering the lithium silicate composite particles located at a position of 0.75TA from the surface of the current collector of the active material layer satisfy T1b>T1t. The surface of the current collector is synonymous with the interface between the active material layer and the current collector. The position of 0.25TA from the surface of the current collector of the active material layer is synonymous with the position of 0.25TA from the interface between the active material layer and the current collector. The position of 0.75TA from the surface of the current collector of the active material layer is synonymous with the position of 0.75TA from the interface between the active material layer and the current collector.

[0013] The thickness T1b and the thickness T1t may satisfy 0.02≦T1t / T1b<1, 0.2≦T1t / T1b≦0.8, or 0.2≦T1t / T1b≦0.5.

[0014] The thicknesses T1b and T1t of the first coating can be measured by observing the cross section of the active material particles using an SEM or TEM.

[0015] First, the electrochemical device is disassembled to take out the electrochemical element (e.g., electrode), and a cross section of the element is obtained using a cross section polisher (CP). In the image of the cross section obtained using SEM or TEM, when the thickness of the active material layer is TA, 10 lithium silicate composite particles that overlap a line drawn from the surface of the current collector of the active material layer to a position of 0.25TA and have a maximum diameter of 5 μm or more are selected. For each particle, the thickness of the first coating is measured at one or two intersections between the line and the outer edge of the lithium silicate composite particle. The average value of the thicknesses at up to 20 points is calculated. After calculating this average value, data that differs from the obtained average value by 20% or more is excluded, and the average value is calculated again. This corrected average value is the thickness T1b of the first coating at the 0.25TA point. Similarly, the thickness T1t of the first coating at the 0.75TA point is calculated using a line drawn from the surface of the current collector of the active material layer to a position of 0.75TA.

[0016] The starting point of the first coating is the interface between the mother particle (see below) formed by the lithium silicate composite particle and the first coating. For example, the starting point of the first coating can be regarded as a point where the intensity of the peak attributed to Li obtained by SEM-EDS analysis is 1 / 10 or less of the peak attributed to the first element. The end point of the first coating can be regarded as a point where the intensity of the peak attributed to the first element obtained by SEM-EDS analysis is 5% or less of its maximum value. When the second coating is formed, the end point of the first coating is the interface between the first coating and the second coating.

[0017] The thickness of the first coating film changes so as to become thinner from the surface of the current collector toward the outside. This change may be continuous or stepwise, and may be any thickness that can be understood as an overall trend.

[0018] For example, lithium silicate composite particles are selected at multiple locations (e.g., five locations) on a line in the thickness direction of the active material layer at different distances from the surface of the current collector, and the thickness of the first coating is measured at one or two intersections between the line and the outer edge of the lithium silicate composite particle. Multiple lines (e.g., five lines) are drawn in the thickness direction of the active material layer, and the thickness of the first coating is measured in the same manner. The thickness calculated in this manner is plotted on a graph with the horizontal axis representing the distance from the surface of the current collector and the vertical axis representing the thickness. From this graph, if the approximation line or approximation curve obtained by the least squares method slopes downward to the right, it can be determined that the thickness of the first coating generally tends to decrease from the surface of the current collector toward the outside.

[0019] The first coating can improve the chemical stability of the lithium silicate composite particles, thereby suppressing deterioration of the electrochemical element and providing an electrochemical device with high capacity and long life.

[0020] The electrochemical element may be an electrode. The electrode may be, for example, at least one of a positive electrode and a negative electrode used in a secondary battery. The electrode according to the embodiment of the present disclosure is preferably used as a negative electrode for a lithium ion secondary battery.

[0021] [Current collector] As the current collector, a non-porous conductive substrate (such as a metal foil) or a porous conductive substrate (such as a mesh, net, or punched sheet) is used.

[0022] [Active material layer] The active material layer includes active material particles. The active material particles include lithium silicate composite particles including a lithium silicate phase and silicon particles dispersed within the lithium silicate phase, and a first coating that covers at least a portion of the surface of the lithium silicate composite particles. The active material layer is formed on a surface of a current collector. The active material layer may be formed on one surface or both surfaces of the current collector.

[0023] (Lithium silicate composite particles) The lithium silicate composite particles include a lithium silicate phase and silicon particles dispersed in the lithium silicate phase. The lithium silicate composite particles have a lithium silicate phase that is the sea portion of a sea-island structure, and silicon particles that are the island portions.

[0024] The lithium silicate composite particles are typically present as secondary particles formed by agglomeration of multiple primary particles. The first coating covers at least a portion of the surface of the secondary particles. Each primary particle comprises a silicate phase and silicon particles dispersed within the silicate phase.

[0025] The particle size of the lithium silicate composite particles is not particularly limited. The average particle size of the lithium silicate composite particles may be, for example, 1 μm or more and 20 μm or less. The average particle size of the lithium silicate composite particles means the particle size (volume average particle size) at which the volume integrated value is 50% in the volume particle size distribution measured by the laser diffraction scattering method.

[0026] 〈Lithium silicate phase〉 Since the lithium silicate phase (hereinafter sometimes simply referred to as the silicate phase) has few sites that can react with lithium, it is difficult to cause a new irreversible reaction during charge and discharge. Therefore, it exhibits excellent charge and discharge efficiency at the initial stage of charge and discharge.

[0027] The silicate phase is an oxide phase containing Li, Si, and O. The atomic ratio of O to Si (=O / Si) in the silicate phase is, for example, greater than 2 and less than 3. When O / Si is within this range, it is advantageous in terms of stability and lithium ion conductivity.

[0028] The silicate phase is Li 2z SiO 2+z (where z is 0 < z < 1). From the viewpoints of stability, ease of production, lithium ion conductivity, etc., z = 1 / 2 is more preferable.

[0029] The silicate phase may further contain an element M. Here, M can be, for example, at least one selected from the group consisting of Be, Mg, Al, B, Zr, Nb, Ta, La, V, Y, Ti, P, Bi, Zn, Sn, Pb, Sb, Co, Er, F, and W. Among them, B has a low melting point and is advantageous for improving the fluidity of the molten silicate. Also, Al, Zr, Nb, Ta, and La can improve the Vickers hardness while maintaining the ion conductivity of the silicate phase. The content of element M is, for example, 10 mol% or less, and may be 5 mol% or less, based on the total amount of elements other than O contained in the silicate phase.

[0030] 〈Silicon particles〉 The silicon particles dispersed in the silicate phase have a particulate phase of simple silicon (Si) and are composed of single or multiple crystallites. The crystallite size of the silicon particles is not particularly limited. The crystallite size of the silicon particles is more preferably 10 nm or more and 30 nm or less, and even more preferably 15 nm or more and 25 nm or less. When the crystallite size of the silicon particles is 10 nm or more, the surface area of ​​the silicon particles can be kept small, so that the deterioration of the silicon particles accompanied by the generation of irreversible capacity is unlikely to occur. The crystallite size of the silicon particles is calculated by Scherrer's formula from the half-width of the diffraction peak assigned to the Si (111) plane in the X-ray diffraction (XRD) pattern of the silicon particles.

[0031] In order to increase the capacity and improve the cycle characteristics, the content of silicon particles in the lithium silicate composite particles may be, for example, 30% by mass or more and 80% by mass or less. By making the content of silicon particles 30% by mass or more, the proportion of the silicate phase is reduced, and the initial charge / discharge efficiency is likely to be improved. By making the content of silicon particles 80% by mass or less, the degree of expansion and contraction of the lithium silicate composite particles during charge and discharge is likely to be reduced.

[0032] Carbon phase The lithium silicate composite particles may contain a carbon phase together with the lithium silicate phase and the silicon particles. The carbon phase, for example, covers at least a portion of the surface of the silicon particles and is present at at least a portion of the interface between adjacent primary particles.

[0033] The content of each element contained in the lithium silicate composite particles can be calculated, for example, by SEM-EDS analysis using a powder sample of the lithium silicate composite particles in a discharged state. The powder sample is analyzed to measure the spectral intensity of each element. Then, a calibration curve is created using a commercially available standard sample of the element, and the content of each element contained in the silicate phase is calculated.

[0034] Quantitative determination of each element in lithium silicate composite particles is also possible using ICP-AES analysis (inductively coupled plasma atomic emission spectroscopy), Auger electron spectroscopy (AES), laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS), X-ray photoelectron spectroscopy (XPS), etc.

[0035] (First Coating) The first coating covers at least a part of the surface of the lithium silicate composite particle, which is a secondary particle. The first coating contains a first element other than the nonmetallic element.

[0036] The thickness T1b of the first coating that covers the lithium silicate composite particles located at a position of 0.25TA from the surface of the current collector of the active material layer is not particularly limited. From the viewpoint of corrosion inhibition, the thickness T1b may be 0.1 nm or more, 0.5 nm or more, or 1 nm or more. From the viewpoint of electrical conductivity and lithium ion diffusibility, the thickness T1b of the first coating may be 50 nm or less, 10 nm or less, or 2 nm or less. The thickness T1b of the first coating may be, for example, 0.1 nm or more and 50 nm or less, or 0.1 nm or more and 10 nm or less.

[0037] The thickness T1t of the first coating that covers the lithium silicate composite particles located at a distance of 0.75TA from the surface of the current collector of the active material layer is not particularly limited. From the viewpoint of electrical conductivity and lithium ion diffusibility, the thickness T1t may be 50 nm or less, 10 nm or less, or 2 nm or less. From the viewpoint of corrosion inhibition, the thickness T1t may be 0.1 nm or more, 0.5 nm or more, or 1 nm or more. The thickness T1t of the first coating may be, for example, 0.1 nm or more and 50 nm or less, or 0.1 nm or more and 10 nm or less. However, T1t is smaller than T1b.

[0038] Average thickness of the first coating T1 A From the viewpoint of corrosion inhibition, the average thickness T1 of the first coating is not particularly limited. AIn terms of electrical conductivity and lithium ion diffusibility, the average thickness T1 of the first coating film may be 0.1 nm or more, 0.5 nm or more, or 1 nm or more. A The average thickness T1 of the first coating may be 50 nm or less, may be 10 nm or less, or may be 2 nm or less. A is, for example, 0.1 nm or more and 50 nm or less.

[0039] Average thickness of the first coating T1 A can be calculated by averaging the thickness T1b and the thickness T1t.

[0040] The first element is an element other than a nonmetallic element, and includes a metal element and a so-called metalloid element. In particular, in terms of the high corrosion inhibition effect of the lithium silicate composite particles, it is preferable that the first element includes at least one element selected from the group consisting of Group 3 elements, Group 4 elements, Group 5 elements, and Group 6 elements of the periodic table. In particular, it is preferable that the first element includes at least one element selected from the group consisting of Al, Ti, Si, Zr, Mg, Nb, Ta, Sn, Ni, and Cr.

[0041] When two or more kinds of oxides are contained, the oxides may be mixed together or may be arranged in layers.

[0042] It is preferable that the first element is present in a greater amount closer to the surface of the lithium silicate composite particle, which improves the effect of inhibiting corrosion of the lithium silicate composite particle.

[0043] Specifically, when the thickness of the first coating covering any lithium silicate composite particle is T1, it is desirable that the concentration Cb of the first element at a position 0.25T1 from the surface of the lithium silicate composite particle of the first coating and the concentration Ct of the first element at a position 0.75T1 from the surface of the lithium silicate composite particle of the same first coating satisfy Cb>Ct. The surface of the lithium silicate composite particle is synonymous with the interface between the first coating and the lithium silicate composite particle.

[0044] The concentration Cb and the concentration Ct may satisfy Cb / Ct>2.

[0045] The average concentration C of the first element in the first coating A is not particularly limited. A may be, for example, 1% or more, or 3% or more. In other words, the concentration C A is 1% or more, the coating is a first coating containing the first element. A may be, for example, 80% or less, or 50% or less. A can be calculated by averaging the concentrations Cb and Ct.

[0046] The concentration Cb of the first element inside the first coating can be obtained by evaluating the element distribution state (depth profile) using energy dispersive X-ray spectroscopy (EDS). The thickness T1 of the first coating is divided into four equal parts, and the profile at a position 0.25T1 from the surface of the lithium silicate composite particle is evaluated. This evaluation is performed on any other multiple lithium silicate composite particles (e.g., five particles) and the results are averaged to obtain the concentration Cb of the first element at that point.

[0047] Alternatively, the concentration Cb may be determined by evaluating the distribution of the first element in the thickness direction using a combination of X-ray photoelectron spectroscopy (XPS), electron energy-loss spectroscopy (EELS), or Electron Spectroscopy for Chemical Analysis (ESCA)) and ion etching. The concentration Cb may be calculated from the molar fraction of the oxide of the first element in the first coating. The molar fraction can be calculated from the measurement results of EDS or EELS and a calibration curve.

[0048] Similarly, the concentration Ct can be determined by evaluating the profile at a position 0.75T1 from the surface of the lithium silicate composite particle.

[0049] The first coating may contain carbon atoms as well as an oxide of a first element other than a nonmetallic element. This improves the electrical conductivity of the active material particles. It is preferable that the oxide and the carbon atoms are mixed in the first coating.

[0050] The average elemental ratio R of the first element to carbon atoms in the first coating covering any lithium silicate composite particle A (=first element / carbon atom) is not particularly limited. A may be 0.01 or more and 99 or less, and may be 0.1 or more and 3 or less.

[0051] Regardless of whether the first coating does not contain carbon or contains carbon, it is desirable for the first element to be present in greater amounts closer to the surface of the lithium silicate composite particle.

[0052] Specifically, when the thickness of the first coating covering the lithium silicate composite particle is T1, it is desirable that the element ratio Rb (=first element / carbon atom) of the first element to carbon atoms at a position 0.25T1 from the surface of the lithium silicate composite particle of the first coating and the element ratio Rt (=first element / carbon atom) of the first element to carbon atoms at a position 0.75T1 from the surface of the lithium silicate composite particle of the same first coating satisfy Rb>Rt.

[0053] The element ratio Rb and the element ratio Rt may satisfy Rb / Rt>1.3, Rb / Rt>2, or Rb / Rt>3.

[0054] The element ratio Rb of the first element to the carbon atom at a position 0.25T1 from the surface of the lithium silicate composite particle of the first coating is not particularly limited. The element ratio Rb may be, for example, 0.01 or more and 99 or less, or 0.1 or more and 3 or less.

[0055] The element ratio Rt of the first element to the carbon atom at the position 0.75T1 from the surface of the lithium silicate composite particle of the first coating is not particularly limited. The element ratio Rt may be, for example, 0.01 or more and 0.8 or less, 0.01 or more and 0.5 or less, or 0.03 or more and 0.5 or less.

[0056] The element ratio inside the first coating can be obtained by evaluating the element distribution state of the first element and carbon atoms using EDS or the like in the same manner as described above. The average element ratio R A can be calculated by averaging the element ratio Rb and the element ratio Rt.

[0057] Examples of carbon include amorphous carbon with low crystallinity such as carbon black, coal, coke, charcoal, and activated carbon, and graphite with high crystallinity. Among them, amorphous carbon is preferred because it has low hardness and a large buffering effect on silicon particles that change in volume during charging and discharging. The amorphous carbon may be either easily graphitized carbon (soft carbon) or difficult to graphitize carbon (hard carbon). Examples of carbon black include acetylene black and ketjen black. Graphite refers to a material having a graphite-type crystal structure, and examples of the graphite include natural graphite, artificial graphite, and graphitized mesophase carbon particles.

[0058] (Second Coating) At least a portion of the first coating may be covered with a conductive second coating, thereby improving the conductivity of the active material particles.

[0059] The second coating is different from the first coating in that it does not contain an oxide of the first element. The fact that the second coating does not contain an oxide of the first element means that the intensity of the peak attributed to the first element obtained by SEM-EDS is equal to or lower than the detection limit.

[0060] The second coating contains a conductive material. The conductive material is preferably a conductive carbon material in terms of being electrochemically stable. Examples of the conductive carbon material include carbon that can be contained in the first coating as described above.

[0061] The thickness of the second coating is not particularly limited. The second coating is preferably thin to such an extent that it does not substantially affect the average particle size of the lithium silicate composite particles. The average thickness of the second coating may be 1 nm or more, and may be 5 nm or more. The average thickness of the second coating may be 200 nm or less, and may be 100 nm or less. The average thickness of the second coating can be calculated in the same manner as the average thickness of the first coating.

[0062] The average thickness T1 of the first coating A and the average thickness T2 of the second coating A satisfy the relationship of 0 < T2 A / T1 A < 1500, which is preferably satisfied. T2 A / T1 A is preferably 5 or more, and preferably 10 or more. T2 A / T1 A is preferably 500 or less, and preferably 100 or less.

[0063] The starting point of the second coating is the interface with the first coating. The end point of the second coating is the outermost point of the active material particles that can be confirmed by SEM or TEM images. The end point of the second coating is, alternatively, the point at which the intensity of the peak attributed to C obtained by SEM-EDS analysis becomes 5% or less of its maximum value.

[0064] It is also preferable that the thickness T1 of the first coating and the thickness T2 of the second coating that cover any lithium silicate composite particles satisfy the relationship of 0 < T2 / T1 < 1500. This makes it easier to achieve both corrosion resistance and improved conductivity. T2 / T1 is preferably 5 or more, and preferably 10 or more. T2 / T1 is preferably 500 or less, and preferably 100 or less.

[0065] The thicknesses of the first and second coatings covering any lithium silicate composite particle can be measured by observing the cross section of the lithium silicate composite particle using SEM or TEM, in the same manner as when determining the average thickness of the first coating. From the cross-sectional image of the electrochemical device obtained in the same manner as above, one active material particle with a maximum diameter of 5 μm or more is randomly selected, and the thicknesses of the first and second coatings at any five points are measured. The average values ​​of the thicknesses at each of these five points are calculated. The average values ​​are taken as the thicknesses T1 and T2 of the first and second coatings covering any lithium silicate composite particle.

[0066] Fig. 1 is a schematic cross-sectional view showing a main part of an electrochemical device according to an embodiment of the present disclosure, Fig. 2 is a schematic cross-sectional view showing a further enlarged view of the main part of the electrochemical device shown in Fig. 1.

[0067] The electrochemical device 10 includes a current collector 11 and an active material layer 12. The active material layer 12 includes active material particles 20. The active material particles 20 include lithium silicate composite particles 23 and a first coating 27 covering the surfaces thereof.

[0068] A method for calculating the thickness T1b of the first coating 27 that covers the lithium silicate composite particle 23 located at a position 0.25TA from the surface of the current collector 11 of the active material layer 12 will be described with reference to Fig. 2. For convenience, only two lithium silicate composite particles are shown in Fig. 2. The thickness T1t can be calculated in the same manner.

[0069] When the thickness of the active material layer is TA, 10 lithium silicate composite particles 23 that overlap a line drawn from the surface of the current collector of the active material layer to a position 0.25TA and have a maximum diameter of 5 μm or more are selected. For each particle, the thickness of the first coating is measured at one or two intersections between the line and the outer edge of the lithium silicate composite particle (T11, T12, T13, T14, ...). The average value of the thicknesses at up to 20 points is calculated. After calculating this average value, data that differs from the obtained average value by 20% or more is excluded, and the average value is calculated again. This corrected average value is the thickness T1b of the first coating at the point 0.25TA.

[0070] 3 is a schematic cross-sectional view showing in detail a cross section of an example of an active material particle. The lithium silicate composite particle 23 is a secondary particle (parent particle) formed by agglomeration of a plurality of primary particles 24. Each primary particle 24 includes a silicate phase 21 and silicon particles 22 dispersed in the silicate phase 21. The silicon particles 22 are dispersed approximately uniformly in the silicate phase 21.

[0071] A carbon phase (not shown) is disposed on at least a part of the interface S between adjacent primary particles 24. At least a part of the surface of the silicon particle 22 may be covered with the carbon phase.

[0072] The surface of the lithium silicate composite particle (base particle) 23 is covered with a first coating 27. The first coating 27 is covered with a second coating 26.

[0073] B. Electrochemical Devices The electrochemical device according to the embodiment of the present disclosure includes a first electrode, a second electrode, and a separator interposed therebetween. One of the first electrode and the second electrode is formed of the electrochemical element described above. Such an electrochemical device has a high capacity and a long life.

[0074] An electrochemical device is a device that transfers electrons between substances to cause a chemical reaction. Examples of electrochemical devices include primary batteries, secondary batteries, capacitors, and air double layer capacitors. The electrochemical device according to the embodiment of the present disclosure is preferably a lithium ion secondary battery that uses lithium silicate composite particles as a negative electrode active material.

[0075] Hereinafter, the configurations of the negative electrode as the electrochemical element according to the embodiment of the present disclosure and the lithium ion secondary battery as the electrochemical device will be specifically described.

[0076] [Negative electrode] The negative electrode includes, for example, a negative electrode current collector and a negative electrode active material layer.

[0077] The negative electrode active material layer includes a negative electrode active material. The negative electrode active material includes at least the above-mentioned active material particles (hereinafter, may be referred to as a first active material). The negative electrode active material layer is formed as a layer including a negative electrode mixture on the surface of a negative electrode current collector. The negative electrode active material layer may be formed on one surface or both surfaces of the negative electrode current collector. The negative electrode mixture includes the negative electrode active material as an essential component, and may include a binder, a conductive agent, a thickener, and the like as optional components.

[0078] The negative electrode active material may further include another active material (hereinafter, sometimes referred to as a second active material). An example of the second active material is a conductive carbon material that electrochemically absorbs and releases lithium ions. By using the first active material and the conductive carbon material in combination, a further longer life can be expected.

[0079] Examples of conductive carbon materials include graphite, graphitizable carbon (soft carbon), and non-graphitizable carbon (hard carbon). Among them, graphite is preferred because of its excellent charge / discharge stability and low irreversible capacity. Graphite means a material having a graphite-type crystal structure, and includes, for example, natural graphite, artificial graphite, and graphitized mesophase carbon particles. The conductive carbon materials may be used alone or in combination of two or more.

[0080] The particle size of the conductive carbon material is not particularly limited. The average particle size of the conductive carbon material may be, for example, 1 μm or more and 30 μm or less.

[0081] The proportion of the first active material in the total of the first and second active materials may be, for example, 3% by mass to 30% by mass, which makes it easier to achieve both high capacity and long life.

[0082] As the negative electrode current collector, a non-porous conductive substrate (metal foil, etc.) or a porous conductive substrate (mesh, net, punched sheet, etc.) is used. Examples of the material of the negative electrode current collector include stainless steel, nickel, nickel alloy, copper, copper alloy, etc. The thickness of the negative electrode current collector is not particularly limited, but is preferably 1 μm or more and 50 μm or less, more preferably 5 μm or more and 20 μm or less, from the viewpoint of the balance between the strength and weight reduction of the negative electrode.

[0083] The binder may be, for example, at least one selected from the group consisting of polyacrylic acid, polyacrylic acid salts, and derivatives thereof. As the polyacrylic acid salts, Li salts or Na salts are preferably used. Among them, it is preferable to use crosslinked lithium polyacrylate.

[0084] Examples of conductive agents include carbon blacks such as acetylene black, conductive fibers such as carbon fibers and metal fibers, carbon fluoride, metal powders such as aluminum, conductive whiskers such as zinc oxide and potassium titanate, conductive metal oxides such as titanium oxide, and organic conductive materials such as phenylene derivatives. These may be used alone or in combination of two or more.

[0085] Examples of thickeners include carboxymethylcellulose (CMC) and its modified products (including salts such as Na salt), cellulose derivatives such as methylcellulose (cellulose ethers, etc.), saponified polymers having vinyl acetate units such as polyvinyl alcohol, polyethers (polyalkylene oxides such as polyethylene oxide, etc.), etc. These may be used alone or in combination of two or more.

[0086] [Positive electrode] The positive electrode includes, for example, a positive electrode current collector and a positive electrode active material layer formed on the surface of the positive electrode current collector. The positive electrode active material layer may be formed on one surface or both surfaces of the positive electrode current collector.

[0087] The positive electrode active material layer is formed as a layer containing a positive electrode mixture on the surface of a positive electrode current collector. The positive electrode mixture contains a positive electrode active material as an essential component, and may contain a binder, a conductive agent, and the like as optional components.

[0088] The positive electrode active material may be a lithium composite metal oxide. For example, Li a CoO2, Li a NiO2, Li a MnO2, Li a Co b Ni 1-b O2, Li a Co b M 1-b O c , Li a Ni 1-b M b O c , Li a Mn2O4, Li a Mn 2-b M b O 4、 LiMePO 4、Li2MePO4F is an example. Here, M is at least one selected from the group consisting of Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb, and B. Me contains at least a transition element (e.g., at least one selected from the group consisting of Mn, Fe, Co, and Ni). 0≦a≦1.2, 0≦b≦0.9, and 2.0≦c≦2.3.

[0089] The binder and conductive agent may be the same as those exemplified for the negative electrode. As the conductive agent, graphite such as natural graphite or artificial graphite may be used.

[0090] The shape and thickness of the positive electrode current collector can be selected from the shape and range corresponding to those of the negative electrode current collector. Examples of the material of the positive electrode current collector include stainless steel, aluminum, aluminum alloy, and titanium.

[0091] [Separator] The separator is interposed between the positive electrode and the negative electrode. The separator has high ion permeability and has appropriate mechanical strength and insulation properties. Examples of the separator include a microporous thin film, a woven fabric, and a nonwoven fabric. The separator is made of a polyolefin such as polypropylene or polyethylene.

[0092] [Electrolytes] The electrochemical device according to the embodiment of the present disclosure further includes an electrolyte. The electrolyte includes a solvent and a lithium salt dissolved in the solvent. The concentration of the lithium salt in the electrolyte is, for example, 0.5 mol / L or more and 2 mol / L or less. The electrolyte may contain a known additive.

[0093] The solvent used may be an aqueous solvent or a non-aqueous solvent. Examples of the non-aqueous solvent include cyclic carbonates, chain carbonates, and cyclic carboxylates. Examples of the cyclic carbonates include propylene carbonate (PC) and ethylene carbonate (EC). Examples of the chain carbonates include diethyl carbonate (DEC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC). Examples of the cyclic carboxylates include γ-butyrolactone (GBL) and γ-valerolactone (GVL). The non-aqueous solvents may be used alone or in combination of two or more.

[0094] Examples of lithium salts include lithium salts of chlorine-containing acids (LiClO4, LiAlCl4, LiB 10 Cl 10 etc.), lithium salts of fluorine-containing acids (LiPF6, LiBF4, LiSbF6, LiAsF6, LiCF3SO3, LiCF3CO2, etc.), lithium salts of fluorine-containing acid imides (LiN(SO2F)2, LiN(CF3SO2)2, LiN(CF3SO2)(C4F9SO2), LiN(C2F5SO2)2, etc.), lithium halides (LiCl, LiBr, LiI, etc.), etc. The lithium salts may be used alone or in combination of two or more.

[0095] An example of the structure of the secondary battery is a structure in which an electrode group formed by winding a positive electrode, a negative electrode, and a separator, and an electrolyte are housed in an exterior body. Instead of a wound type electrode group, a laminated type electrode group in which a positive electrode and a negative electrode are laminated with a separator interposed therebetween may be used. In addition, an electrode group of another form may be applied. The secondary battery may be in any form, such as a cylindrical type, a square type, a coin type, a button type, or a laminate type.

[0096] 4 is a schematic perspective view of a partially cutaway prismatic secondary battery according to an embodiment of the present disclosure. The battery includes a bottomed prismatic battery case 4, an electrode group 1 and an electrolyte (not shown) housed in the battery case 4, and a sealing plate 5 that seals the opening of the battery case 4. The electrode group 1 includes a long strip-shaped negative electrode, a long strip-shaped positive electrode, and a separator interposed therebetween. The negative electrode, positive electrode, and separator are wound around a flat winding core, and the electrode group 1 is formed by removing the winding core. The sealing plate 5 includes a liquid injection port closed by a plug 8 and a negative electrode terminal 6 insulated from the sealing plate 5 by a gasket 7.

[0097] One end of a negative electrode lead 3 is attached to the negative electrode current collector of the negative electrode by welding or the like. One end of a positive electrode lead 2 is attached to the positive electrode current collector of the positive electrode by welding or the like. The other end of the negative electrode lead 3 is electrically connected to a negative electrode terminal 6. The other end of the positive electrode lead 2 is electrically connected to a sealing plate 5. A resin frame is disposed on the upper part of the electrode group 1 to separate the electrode group 1 from the sealing plate 5 and to separate the negative electrode lead 3 from the battery case 4.

[0098] C. Manufacturing method of electrochemical element A manufacturing method for an electrochemical element according to an embodiment of the present disclosure includes a preparation step of preparing lithium silicate composite particles containing a silicate phase and silicon particles dispersed within the silicate phase, a support step of supporting the lithium silicate composite particles on a surface of a current collector, and, after the support step, a coating formation step of exposing the lithium silicate composite particles to a gas phase containing a first element other than non-metallic elements to form a first coating containing an oxide of the first element on at least a portion of the surface.

[0099] FIG. 5 is a flowchart showing a method for producing active material particles according to one embodiment of the present disclosure.

[0100] (I) Preparation step of lithium silicate composite particles (S1) (Ii) Preparation of silicon particles First, silicon particles are prepared.

[0101] Silicon particles can be obtained by chemical vapor deposition (CVD), thermal plasma, physical pulverization, etc. In the following method, silicon nanoparticles with an average particle size of 10 to 200 nm, for example, can be synthesized. The average particle size of silicon particles means the particle size (volume average particle size) at which the volume integrated value is 50% in the volume particle size distribution measured by the laser diffraction scattering method.

[0102] (a) Chemical vapor deposition In the CVD method, for example, a silane compound is oxidized or reduced in a gas phase to generate silicon particles. The reaction temperature may be set to, for example, 400° C. or higher and 1300° C. or lower.

[0103] Examples of the silane compound include silicon hydrides such as silane and disilane, halogenated silanes, and alkoxysilanes. Examples of the halogenated silanes include dichlorosilane, trichlorosilane, and tetrachlorosilane. Examples of the alkoxysilanes include tetramethoxysilane, tetraethoxysilane, and tetrabutoxysilane.

[0104] For example, when silicon hydride is contacted with an oxidizing gas in the gas phase, a composite of silicon particles and silicon oxide particles is obtained. That is, the gas phase atmosphere may be an oxidizing gas atmosphere. The composite is washed with, for example, hydrofluoric acid to remove the silicon oxide and obtain silicon particles.

[0105] When reducing halogenated silanes, alkoxysilanes, etc., it is sufficient to contact a silane compound with molten metal that has been finely atomized by an atomization method. Na, K, Mg, Ca, Zn, Al, etc. can be used as the molten metal. An inert gas, halogenated silane, hydrogen gas, etc. can be used as the atomization gas. That is, the gas phase atmosphere can be an inert gas or reducing gas atmosphere.

[0106] (b) Thermal plasma method The thermal plasma method is a method in which silicon raw material is introduced into generated thermal plasma and silicon particles are generated in the high-temperature plasma. Thermal plasma can be generated by arc discharge, high-frequency discharge, microwave discharge, laser light irradiation, etc. Among these, radio-frequency (RF) discharge is desirable because it is a non-polarized discharge and impurities are less likely to become mixed into the silicon particles.

[0107] The raw material may be, for example, silicon oxide. When the raw material is introduced into the plasma, silicon and oxygen in atomic or ionic states are instantly generated, and the silicon bonds and solidifies during cooling to generate silicon particles.

[0108] (c) Physical crushing method The physical pulverization method (mechanical milling method) is a method in which coarse silicon particles are pulverized by a pulverizer such as a ball mill, a bead mill, etc. The inside of the pulverizer may be, for example, an inert gas atmosphere.

[0109] (I-ii) Coating of silicon particles with carbon phase At least a portion of the surface of the silicon particles may be coated with a carbon phase.

[0110] Methods for coating silicon particles with a carbon phase include chemical vapor deposition (CVD), sputtering, atomic layer deposition (ALD), wet mixing, dry mixing, etc. Among these, CVD and wet mixing are preferred.

[0111] (a) Chemical vapor deposition In the CVD method, silicon particles are introduced into a hydrocarbon gas atmosphere, which is then heated to deposit the carbon material produced by pyrolysis of the hydrocarbon gas on the particle surface, forming a carbon phase. The temperature of the hydrocarbon gas atmosphere may be, for example, 500°C to 1000°C. As the hydrocarbon gas, chain hydrocarbon gases such as acetylene and methane, and aromatic hydrocarbons such as benzene, toluene, and xylene may be used.

[0112] (b) Wet mixing method In the wet mixing method, a carbon precursor such as coal pitch, petroleum pitch, or tar is dissolved in a solvent, and the resulting solution is mixed with silicon particles and dried. The silicon particles coated with the carbon precursor are then heated in an inert gas atmosphere at a temperature of, for example, 600° C. to 1000° C. to carbonize the carbon precursor and form a carbon phase.

[0113] (I-iii) Synthesis of lithium silicate composite particles A silicate phase raw material is prepared.

[0114] The raw material for the silicate phase may be a raw material mixture containing a Si raw material and a Li raw material in a specified ratio. The raw material mixture is melted and the molten liquid is passed through a metal roll to form flakes, to obtain silicate. Alternatively, the raw material mixture may not be melted, but may be fired at a temperature below the melting point to synthesize silicate through a solid-phase reaction.

[0115] Silicon oxide (e.g., SiO2) can be used as the Si raw material. Carbonates, oxides, hydroxides, hydrides, nitrates, sulfates, etc. of lithium or element M can be used as the Li raw material or element M raw material. Among them, carbonates, oxides, hydroxides, etc. are preferred.

[0116] Next, silicon particles at least part of whose surface is coated with a carbon phase (hereinafter also referred to as carbon-coated silicon particles) are blended with the silicate and the two are mixed. For example, lithium silicate composite particles are produced through the following steps.

[0117] First, carbon-coated silicon particles and silicate powder are mixed in a mass ratio of, for example, 20:80 to 95:5.

[0118] Next, the mixture of carbon-coated silicon particles and silicate is stirred using a device such as a ball mill. At this time, it is preferable to add an organic solvent to the mixture and wet mix it. A predetermined amount of organic solvent may be charged into the grinding vessel all at once at the beginning of grinding, or may be charged into the grinding vessel intermittently in multiple batches during the grinding process. The organic solvent serves to prevent the material to be ground from adhering to the inner wall of the grinding vessel. As the organic solvent, alcohol, ether, fatty acid, alkane, cycloalkane, silicate ester, metal alkoxide, etc. can be used.

[0119] The mixture is then sintered by heating at 450°C to 1000°C under pressure in an inert gas atmosphere (e.g., argon, nitrogen, etc.). For sintering, a sintering device capable of applying pressure in an inert atmosphere, such as a hot press or spark plasma sintering, can be used. During sintering, the silicate melts and flows to fill the gaps between the silicon particles. As a result, a dense block-shaped sintered body can be obtained, with the silicate phase as the sea portion and the silicon particles as the islands.

[0120] Finally, the sintered body is pulverized to obtain lithium silicate composite particles. By appropriately selecting the pulverization conditions, lithium silicate composite particles having a predetermined average particle size can be obtained.

[0121] (I-iv) Coating of lithium silicate composite particles with carbon films At least a portion of the surface of the lithium silicate composite particle may be coated with a carbon coating, and the carbon atoms contained in the first coating are derived from the carbon coating.

[0122] Examples of methods for forming a carbon coating on the surface of lithium silicate composite particles include a chemical vapor deposition method using a chain hydrocarbon gas such as acetylene or methane as a raw material, and a method in which coal pitch, petroleum pitch, phenol resin, or the like is mixed with lithium silicate composite particles and heated to carbonize them. Carbon black may be attached to the surface of the lithium silicate composite particles.

[0123] The carbon coating is preferably thin enough that it does not substantially affect the average particle size of the lithium silicate composite particles. On the other hand, considering that the carbon coating is a carbon source for the first coating, the thickness of the carbon coating is desirably equal to or greater than the desired first coating. The carbon coating may be 0.1 nm or more, or may be 1 nm or more. Considering the diffusibility of lithium ions, the carbon coating is preferably 300 nm or less, more preferably 200 nm or less. The thickness of the carbon coating can be measured by observing the cross section of the lithium silicate composite particles using a SEM or TEM, similar to the first coating.

[0124] Finally, a step of washing the lithium silicate composite particles having the carbon coating with an acid may be performed. For example, by washing the composite particles with an acidic aqueous solution, it is possible to dissolve and remove trace amounts of alkaline components that may be present on the surface of the lithium silicate composite particles. As the acidic aqueous solution, an aqueous solution of an inorganic acid such as hydrochloric acid, hydrofluoric acid, sulfuric acid, nitric acid, phosphoric acid, or carbonic acid, or an aqueous solution of an organic acid such as citric acid or acetic acid can be used.

[0125] (II) Lithium silicate composite particle supporting step (S2) A slurry in which the prepared negative electrode mixture containing the lithium silicate composite particles is dispersed in a dispersion medium is applied to the surface of the current collector, and the slurry is dried, thereby forming a precursor layer of the active material layer on the surface of the current collector.

[0126] The dispersion medium is not particularly limited, but examples thereof include water, alcohols such as ethanol, ethers such as tetrahydrofuran, amides such as dimethylformamide, N-methyl-2-pyrrolidone (NMP), and mixed solvents thereof.

[0127] (III) Step of forming first coating (S3) The lithium silicate composite particles are exposed to a gas phase containing a first element. As a result, a first coating containing an oxide of the first element is formed on at least a portion of the surface of the lithium silicate composite particles. When the lithium silicate composite particles have a carbon coating, this step introduces the first element into the carbon coating to form a first coating containing an oxide of the first element and carbon atoms.

[0128] Examples of the gas phase method include CVD, ALD, and physical vapor deposition (PVD). In particular, the ALD method is preferred because it can form the first coating at a relatively low temperature. According to the ALD method, the first coating can be formed in an atmosphere of 200° C. or less.

[0129] In the ALD method, an organometallic compound (precursor) containing a first element is used as the raw material for the first coating. In the ALD method, a vaporized precursor (raw material gas) and an oxidizing agent are alternately supplied to a reaction chamber in which an object is placed. This forms a layer containing an oxide of the first element on the surface of the object.

[0130] When at least a portion of the surface of the lithium silicate composite particle, which is the target, is covered with a carbon coating, the first element contained in the raw material gas can pass through the carbon coating and reach the surface of the lithium silicate composite particle. The first element is then deposited as is on the surface of the lithium silicate composite particle. Therefore, the first element is likely to be located more in the vicinity of the surface of the lithium silicate composite particle. In this case, the formed first coating contains carbon atoms derived from the carbon coating as well as an oxide of the first element.

[0131] In the ALD method, the self-limiting effect works, so the first element is deposited on the surface of the target object in atomic layers. In the ALD method, the thickness of the first coating is controlled by the number of cycles, which is one cycle of supplying source gas (pulse) → exhausting source gas (purge) → supplying oxidizing agent (pulse) → exhausting oxidizing agent (purge).

[0132] When a carbon coating is present, the oxide of the first element can be distributed over the entire carbon coating by controlling the thickness of the first coating to be approximately the same as that of the carbon coating. When the thickness of the first coating is controlled to be thinner than that of the carbon coating, a first coating containing an oxide of the first element and carbon atoms is formed on the surface side of the lithium silicate composite particle, and a second coating derived from the remainder of the carbon coating is formed to cover this first coating.

[0133] The precursor is an organometallic compound containing the first element. As the precursor, various organometallic compounds that have been conventionally used in the ALD method can be used.

[0134] An example of a precursor containing Ti is bis(t-butylcyclopentadienyl)titanium(IV) dichloride (C 18 H 26 C l2 Examples of the precursors containing Al include trimethylaluminum ((CH3)3Al, TMA).

[0135] The source gas may contain a plurality of types of precursors. Different types of precursors may be supplied to the reaction chamber simultaneously or sequentially. Alternatively, the type of precursor contained in the source gas may be changed for each cycle.

[0136] The oxidizing agent may be any oxidizing agent that has been used in the ALD method. Examples of the oxidizing agent include water, oxygen, ozone, etc. The oxidizing agent may be supplied to the reaction chamber as plasma using the oxidizing agent as a raw material.

[0137] The conditions of the ALD method are not particularly limited. In order to facilitate the formation of a thicker first coating on the lithium silicate composite particles in the vicinity of the current collector, the temperature of the atmosphere containing the precursor or the oxidizing agent may be 10° C. or higher and 200° C. or lower, or 25° C. or higher and 200° C. or lower. From the same viewpoint, it is preferable to use a 1×10 -5 Pa or more 1×10 5 Pa or less, and -4 Pa or more 1×10 4 Pa or less.

[0138] In order to facilitate the formation of a thicker first coating on the lithium silicate composite particles in the vicinity of the current collector, the temperature of the atmosphere containing the precursor or the oxidizing agent in the reaction chamber is set to 10° C. or higher and 200° C. or lower, and the pressure in the reaction chamber during the treatment is set to 1×10 -5 Pa or more 1×10 5 When the pressure is 0.0 Pa or less, the pulse time of the source gas may be 0.005 seconds or more, 0.01 seconds or more, or 0.05 seconds or more. The pulse time of the source gas may be 5 seconds or less, or 3 seconds or less.

[0139] After the first coating is formed, the active material layer may be rolled. The conditions for rolling are not particularly limited and may be appropriately set so that the active material layer has a predetermined thickness or density.

[0140] Hereinafter, the present disclosure will be specifically described based on examples and comparative examples, but the present disclosure is not limited to the following examples.

[0141] Example 1 [Preparation of negative electrode] (1) Preparation of silicon particles Coarse silicon particles (3N, average particle size 10 μm) were loaded into a pot (made of SUS, volume 500 mL) of a planetary ball mill (manufactured by Fritsch, P-5), 24 SUS balls (diameter 20 mm) were placed in the pot, the lid was closed, and the mixture was ground at 200 rpm in an inert atmosphere until the average particle size became 150 nm, to prepare silicon particles.

[0142] (2) Coating of silicon particles with carbon phase A carbon material was deposited on the surface of silicon particles by chemical vapor deposition. Specifically, silicon particles were introduced into an acetylene gas atmosphere and heated at 700°C to pyrolyze the acetylene gas and deposit it on the surface of the silicon particles, forming a carbon phase. The amount of carbon material per 100 parts by mass of silicon particles was 10 parts by mass.

[0143] (3) Preparation of lithium silicate composite particles Silicon dioxide and lithium carbonate were mixed so that the atomic ratio (=Si / Li) was 1.05, and the mixture was fired in air at 950°C for 10 hours to obtain lithium silicate represented by Li2Si2O5 (z=0.5). The obtained lithium silicate was pulverized to an average particle size of 10 μm.

[0144] Lithium silicate (Li2Si2O5) with an average particle size of 10 μm and carbon-coated silicon were mixed in a mass ratio of 70:30. The mixture was charged into a pot (made of SUS, volume 500 mL) of a planetary ball mill (manufactured by Fritsch, P-5), 24 SUS balls (diameter 20 mm) were placed in the pot, the lid was closed, and the mixture was stirred at 200 rpm for 50 hours in an inert atmosphere.

[0145] Next, the powder mixture was taken out in an inert atmosphere, and sintered at 800°C for 4 hours in an inert atmosphere while applying pressure with a hot press machine to obtain a sintered body of the mixture. The sintered body was then pulverized to obtain lithium silicate composite particles.

[0146] The crystallite size of the silicon particles was calculated to be 15 nm using the Scherrer formula from the diffraction peaks assigned to the Si(111) plane by XRD analysis. In the silicate phase, the Si / Li ratio was 1.0, and the content of Li2Si2O5 measured by Si-NMR was 70 mass% (the content of silicon particles was 30 mass%).

[0147] (4) Coating of lithium silicate composite particles with carbon film The obtained lithium silicate composite particles were passed through a 40 μm mesh and then mixed with coal pitch (MCP250, manufactured by JFE Chemical Corporation). The mixture of the lithium silicate composite particles and pitch was fired at 800° C. for 5 hours in an inert atmosphere to form a carbon coating on the surface of the lithium silicate composite particles. The amount of the carbon coating was 5 mass % based on the total mass of the lithium silicate composite particles and the carbon coating. Then, using a sieve, particles having an average particle size of 10 μm and comprising the lithium silicate composite particles and the carbon coating formed on the surface thereof were separated. The thickness of the carbon coating was 50 nm.

[0148] (5) Preparation of negative electrode precursor The lithium silicate composite particles with a carbon coating and a second active material (graphite) were mixed in a mass ratio of 5:95 to be used as the negative electrode active material. Water was added to a negative electrode mixture containing the negative electrode active material, sodium carboxymethylcellulose (CMC-Na), styrene butadiene rubber (SBR), and lithium polyacrylate in a mass ratio of 96.5:1:1.5:1, and then the mixture was stirred using a mixer (TK Hivismix, manufactured by Primix Corporation) to prepare a negative electrode slurry. Next, a 1 m thick layer was applied to the surface of the copper foil. 2 The negative electrode slurry was applied so that the mass of the negative electrode mixture per layer was 190 g, and the coating was dried to form a precursor layer.

[0149] (6) Formation of the first and second coatings The negative electrode precursor was placed in a predetermined reaction chamber, and a first coating was formed on the surface of the negative electrode precursor by an ALD method according to the following procedure.

[0150] The precursor (TDMAT) serving as the source of the first element (Ti) was vaporized and supplied to the reaction chamber containing the negative electrode precursor. The pulse time was 1.0 second. The temperature of the atmosphere containing the precursor in the reaction chamber was controlled at 200°C, and the pressure was controlled at 260 Pa. After 30 seconds, the surface of the negative electrode precursor was covered with a monolayer of the precursor, and the excess precursor was purged with nitrogen gas.

[0151] Next, an oxidant (HO) was vaporized and supplied to the reaction chamber containing the negative electrode precursor. The pulse time was 0.015 seconds. The temperature of the atmosphere containing the oxidant was controlled at 200°C, and the pressure was controlled at 260 Pa. After 30 seconds, the excess oxidant was purged with nitrogen gas.

[0152] A series of operations consisting of supplying a precursor, purging, supplying an oxidizing agent, and purging was repeated 200 times to form a first coating containing titanium. The first coating was adjusted to be thinner than the carbon coating, and the first coating and a second coating covering the first coating were formed simultaneously.

[0153] Thereafter, the obtained negative electrode was rolled to reduce the density of the negative electrode active material layer on both sides of the copper foil to 1.5 g / cm 3 The thickness of the negative electrode active material layer was 202 μm.

[0154] The first coating was analyzed by SEM, EDS, ICP, etc. The first coating contained Ti and C. The thickness T1b of the first coating covering the lithium silicate composite particles located at a position 0.25TA from the surface of the current collector of the active material layer was 10 nm. The thickness T1t of the first coating covering the lithium silicate composite particles located at a position 0.75TA from the surface of the current collector of the active material layer was 6 nm. The average thickness T1 of the first coating A was 8 nm.

[0155] In the first coating covering the lithium silicate composite particle located at a position 0.25TA from the surface of the current collector of the active material layer, the concentration Cb of the first element at a position 0.25T1 from the surface of the lithium silicate composite particle of the first coating was 6%. In the same first coating, the concentration Ct of the first element at a position 0.75T1 from the surface of the lithium silicate composite particle of the first coating was 2%.

[0156] In the first coating covering the lithium silicate composite particle located at a position 075TA from the surface of the current collector of the active material layer, the concentration Cb of the first element at a position 0.25T1 from the surface of the lithium silicate composite particle of the first coating was 3%. In the same first coating, the concentration Ct of the first element at a position 0.75T1 from the surface of the lithium silicate composite particle of the first coating was 0.5%.

[0157] The minimum value of the element ratio R of the first element to the carbon atom is 0.02, the maximum value is 0.2, and the average element ratio R A The thickness of the first coating was about 0.25T1 from the surface of the lithium silicate composite particle. A The element ratio Rb of the first element to the carbon atom at the position was 0.2. A The element ratio Rt of the first element to the carbon atom at the position was 0.02.

[0158] The composition of the second coating was analyzed in the same manner and was found to contain C. In each lithium silicate composite particle, the sum of the thickness of the first coating and the thickness of the second coating was 50 nm.

[0159] The thickness T1 of the first coating covering the lithium silicate composite particles located 0.5 TA from the surface of the current collector in the active material layer was 6 nm, the thickness of the second coating was 44 nm, and the sum of the thicknesses of the first coating and the second coating was 50 nm.

[0160] [Preparation of positive electrode] N-methyl-2-pyrrolidone (NMP) was added to a positive electrode mixture containing lithium cobalt oxide, acetylene black, and polyvinylidene fluoride in a mass ratio of 95:2.5:2.5, and the mixture was stirred using a mixer (TK Hivismix, manufactured by Primix Corporation) to prepare a positive electrode slurry. The positive electrode slurry was then applied to the surface of an aluminum foil, the coating was dried, and the aluminum foil was rolled to form a positive electrode slurry having a density of 3.6 g / cm on both sides of the aluminum foil. 3 A positive electrode having the positive electrode active material layer of the above formula was formed. The thickness of the positive electrode active material layer was 138 μm.

[0161] [Preparation of electrolyte] An electrolyte solution was prepared by dissolving LiPF6 at a concentration of 1.0 mol / L in a mixed solvent containing ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 3:7.

[0162] [Preparation of secondary battery] A tab was attached to each electrode, and the positive and negative electrodes were spirally wound with a separator interposed therebetween so that the tabs were located at the outermost periphery to prepare an electrode group. The electrode group was inserted into an exterior body made of an aluminum laminate film and vacuum dried at 105°C for 2 hours, after which an electrolyte solution was poured in and the opening of the exterior body was sealed to obtain a secondary battery A1.

[0163] Example 2 In the formation of the first and second coatings (6), a first active material was produced in the same manner as in Example 1, except that a series of operations consisting of supplying a precursor, purging, supplying an oxidant, and purging was repeated 100 times. A secondary battery A2 was fabricated by using the first active material.

[0164] The first coating and the second coating were analyzed in the same manner as in Example 1. The first coating covering the lithium silicate composite particles contained Ti and C, and the first coating covering the conductive carbon material contained Ti. The second coating contained C.

[0165] The thickness T1b of the first coating covering the lithium silicate composite particles located 0.25TA from the surface of the current collector of the active material layer was 7 nm. The thickness T1t of the first coating covering the lithium silicate composite particles located 0.75TA from the surface of the current collector of the active material layer was 3 nm. The average thickness T1 of the first coating A For each of the lithium silicate composite particles, the sum of the thickness of the first coating and the thickness of the second coating was 50 nm.

[0166] In the first coating covering the lithium silicate composite particle located at a position 0.25TA from the surface of the current collector of the active material layer, the concentration Cb of the first element at a position 0.25T1 from the surface of the lithium silicate composite particle of the first coating was 10%. In the same first coating, the concentration Ct of the first element at a position 0.75T1 from the surface of the lithium silicate composite particle of the first coating was 7%.

[0167] In the first coating covering the lithium silicate composite particle located at a position 075TA from the surface of the current collector of the active material layer, the concentration Cb of the first element at a position 0.25T1 from the surface of the lithium silicate composite particle of the first coating was 10%. In the same first coating, the concentration Ct of the first element at a position 0.75T1 from the surface of the lithium silicate composite particle of the first coating was 5%.

[0168] The minimum value of the element ratio R of the first element to the carbon atom is 0.01, the maximum value is 0.1, and the average element ratio R A The thickness of the first coating was about 0.06. A The element ratio Rb of the first element to the carbon atom at the position was 0.09. A The element ratio Rt of the first element to the carbon atom at the position was 0.01.

[0169] The thickness T1 of the first coating covering the lithium silicate composite particles located at a distance of 0.5 TA from the surface of the current collector of the active material layer was 3 nm, and the thickness T2 of the second coating was 47 nm.

[0170] Example 3 In the formation of the first and second coatings (6), a series of operations consisting of supplying a precursor, purging, supplying an oxidant, and purging was repeated 44 times, except that a first active material was produced in the same manner as in Example 1, and a secondary battery A3 was fabricated.

[0171] The first coating and the second coating were analyzed in the same manner as in Example 1. The first coating covering the lithium silicate composite particles contained Ti and C, and the first coating covering the conductive carbon material contained Ti. The second coating contained C.

[0172] The thickness T1b of the first coating covering the lithium silicate composite particles located at a position 0.25TA from the surface of the current collector of the active material layer was 2 nm. The thickness T1t of the first coating covering the lithium silicate composite particles located at a position 0.75TA from the surface of the current collector of the active material layer was 1 nm. The average thickness T1 of the first coating A For each of the lithium silicate composite particles, the sum of the thickness of the first coating and the thickness of the second coating was 50 nm.

[0173] In the first coating covering the lithium silicate composite particle located at a position 0.25TA from the surface of the current collector of the active material layer, the concentration Cb of the first element at a position 0.25T1 from the surface of the lithium silicate composite particle of the first coating was 3%. In the same first coating, the concentration Ct of the first element at a position 0.75T1 from the surface of the lithium silicate composite particle of the first coating was 1%.

[0174] In the first coating covering the lithium silicate composite particle located at a position 075TA from the surface of the current collector of the active material layer, the concentration Cb of the first element at a position 0.25T1 from the surface of the lithium silicate composite particle of the first coating was 10%. In the same first coating, the concentration Ct of the first element at a position 0.75T1 from the surface of the lithium silicate composite particle of the first coating was 5%.

[0175] The minimum value of the element ratio R of the first element to the carbon atom is 0.01, the maximum value is 0.2, and the average element ratio R A The thickness of the first coating was about 0.25T1 from the surface of the lithium silicate composite particle. A The element ratio Rb of the first element to the carbon atom at the position was 0.18. A The element ratio Rt of the first element to the carbon atom at the position was 0.015.

[0176] The thickness T1 of the first coating covering the lithium silicate composite particles located at a distance of 0.5 TA from the surface of the current collector in the active material layer was 1 nm, and the thickness T2 of the second coating was 49 nm.

[0177] Example 4 A first active material was produced in the same manner as in Example 2, except that the pulse time of the raw material gas was set to 1.2 seconds, and a secondary battery A4 was fabricated.

[0178] The first coating and the second coating were analyzed in the same manner as in Example 1. The first coating covering the lithium silicate composite particles contained Ti and C, and the first coating covering the conductive carbon material contained Ti. The second coating contained C.

[0179] The thickness T1b of the first coating covering the lithium silicate composite particles located at a position 0.25TA from the surface of the current collector of the active material layer was 10 nm. The thickness T1t of the first coating covering the lithium silicate composite particles located at a position 0.75TA from the surface of the current collector of the active material layer was 3 nm. The average thickness T1 of the first coating A For each of the lithium silicate composite particles, the sum of the thickness of the first coating and the thickness of the second coating was 50 nm.

[0180] In the first coating covering the lithium silicate composite particle located at a position 0.25TA from the surface of the current collector of the active material layer, the concentration Cb of the first element at a position 0.25T1 from the surface of the lithium silicate composite particle of the first coating was 3%. In the same first coating, the concentration Ct of the first element at a position 0.75T1 from the surface of the lithium silicate composite particle of the first coating was 1%.

[0181] In the first coating covering the lithium silicate composite particle located at a position 075TA from the surface of the current collector of the active material layer, the concentration Cb of the first element at a position 0.25T1 from the surface of the lithium silicate composite particle of the first coating was 2%. In the same first coating, the concentration Ct of the first element at a position 0.75T1 from the surface of the lithium silicate composite particle of the first coating was 1%.

[0182] The minimum value of the element ratio R of the first element to the carbon atom is 0.01, the maximum value is 0.05, and the average element ratio R A The thickness of the first coating was about 0.03. A The element ratio Rb of the first element to the carbon atom at the position was 0.04. A The element ratio Rt of the first element to the carbon atom at the position was 0.02.

[0183] The thickness T1 of the first coating covering the lithium silicate composite particles located at a distance of 0.5 TA from the surface of the current collector of the active material layer was 3 nm, and the thickness T2 of the second coating was 47 nm.

[0184] Comparative Example 1 An active material was produced in the same manner as in Example 1, except that the coating of the lithium silicate composite particles with a carbon film (4) and the formation of the first film (6) were not performed, and a secondary battery B1 was fabricated.

[0185] Comparative Example 2 Except for not carrying out the formation of the first coating film (6), an active material was produced in the same manner as in Example 1, and a secondary battery B2 was fabricated.

[0186] Comparative Example 3 An active material was produced in the same manner as in Example 1, except that (4) the coating of the lithium silicate composite particles with a carbon film was not performed, and (6) instead the formation of the first and second coating films was replaced by a treatment using the ALD method on the lithium silicate composite particles before being supported on the copper foil, and a secondary battery B3 was fabricated.

[0187] The treatment of the silicate composite particles using the ALD method was performed under the same conditions as in Example 1, except that a series of operations consisting of precursor supply, purging, oxidant supply, and purging was repeated 100 times. The thickness T1b of the first coating covering the lithium silicate composite particles located at a position 0.25 TA from the surface of the current collector of the active material layer and the thickness T1t of the first coating covering the lithium silicate composite particles located at a position 0.75 TA from the surface of the current collector of the active material layer were both 10 nm.

[0188] [First charge / discharge] Each battery was charged at 25°C at a constant current of 1 C until the voltage reached 4.2 V, and then charged at a constant voltage of 4.2 V until the current reached 1 / 20 C. After a 10-minute rest period, the battery was discharged at a constant current of 1 C until the voltage reached 2.75 V.

[0189] [Charge / discharge cycle test] The battery was repeatedly charged and discharged under the following conditions.

[0190] <Charging> At 25° C., constant current charging was performed at a current of 1 C until the voltage reached 4.2 V, and then constant voltage charging was performed at a voltage of 4.2 V until the current reached 1 / 20 C.

[0191] <Discharge> At 25° C., constant current discharge was performed at a current of 1 C until the voltage reached 2.75 V.

[0192] The rest period between charging and discharging was 10 minutes. The ratio of the discharge capacity at the 100th cycle to the discharge capacity at the 1st cycle was calculated, and the average value for the 20 batteries was obtained. This average value was taken as the capacity retention rate. The evaluation results are shown in Table 1.

[0193] [Table 1]

[0194] It can be seen from Table 1 that the capacity retention rate was greatly improved by using the first active materials A1 to A4. [Industrial Applicability]

[0195] According to the present disclosure, it is possible to provide an electrochemical device having a high capacity and a long life. The electrochemical device according to the present disclosure is useful as a main power source for mobile communication devices, portable electronic devices, and the like. [Explanation of symbols]

[0196] 1 electrode group 2 Positive Lead 3 Negative lead 4 Battery case 5 Sealing plate 6 Negative terminal 7 Gasket 8. Sealing 20 Active material particles 21 Silicate phase 22 Silicon particles 23 Lithium silicate composite particles 24 Primary particles 26 Second Coat 27 First Coat

Claims

1. A battery comprising: a negative electrode current collector; and an active material layer supported on the negative electrode current collector; The active material layer includes active material particles, the active material particles include lithium silicate composite particles including a lithium silicate phase and silicon particles dispersed in the lithium silicate phase, and a first coating film covering at least a portion of a surface of the lithium silicate composite particles; the first coating contains an oxide of a first element other than a nonmetallic element, When the thickness of the active material layer is TA, a thickness T1b of the first coating film that covers the lithium silicate composite particles at a position 0.25 TA from the surface of the negative electrode current collector in the active material layer; a thickness T1t of the first coating film that covers the lithium silicate composite particles at a position 0.75 TA from the surface of the negative electrode current collector of the active material layer; An electrochemical element, wherein T1b>T1t.

2. The thickness T1b and the thickness T1t are The electrochemical element according to claim 1 , wherein 0.02≦T1t / T1b<1 is satisfied.

3. 3. The electrochemical device according to claim 1, wherein the first element comprises at least one element selected from the group consisting of Group 3 elements, Group 4 elements, Group 5 elements, and Group 6 elements of the periodic table.

4. 4. The electrochemical element according to claim 1, wherein the first element includes at least one selected from the group consisting of Al, Ti, Si, Zr, Mg, Nb, Ta, Sn, Ni, and Cr.

5. The average thickness T1 of the first coating A The electrochemical element according to any one of claims 1 to 4, wherein the thickness of the first electrode is 0.1 nm or more and 50 nm or less.

6. When the thickness of the first coating film covering the surface of the lithium silicate composite particle is T1, A concentration Cb of the first element at a position 0.25T1 from the surface of the lithium silicate composite particle of the first coating; The concentration Ct of the first element at a position 0.75T1 from the surface of the lithium silicate composite particle of the first coating is The electrochemical element according to any one of claims 1 to 5, wherein Cb>Ct is satisfied.

7. The electrochemical device according to any one of claims 1 to 6, wherein the first coating further contains carbon atoms.

8. When the thickness of the first coating film covering the surface of the lithium silicate composite particle is T1, an element ratio Rb of the first element to the carbon atom at a position of 0.25T1 from the surface of the lithium silicate composite particle in the first coating; The element ratio Rt of the first element to the carbon atom at a position of 0.75T1 from the surface of the lithium silicate composite particle in the first coating is The electrochemical element according to claim 7 , wherein Rb>Rt is satisfied.

9. 9. The electrochemical element according to claim 1, wherein at least a portion of the first coating is further covered with a second coating having a different electrical conductivity from the first coating.

10. The electrochemical device according to claim 9 , wherein the second coating comprises carbon atoms.

11. When the thickness of the first coating film covering the surface of the lithium silicate composite particle is T1, a thickness T1 of the first coating; The thickness T2 of the second coating is The electrochemical element according to claim 9 or 10, which satisfies the relationship: 0<T1 / T2<1500.

12. The battery includes a first electrode, a second electrode, and a separator disposed therebetween; An electrochemical device, wherein one of the first electrode and the second electrode is constituted by the electrochemical element according to any one of claims 1 to 11.

13. providing a lithium silicate composite particle comprising a lithium silicate phase and silicon particles dispersed within the lithium silicate phase; a supporting step of supporting the lithium silicate composite particles on a surface of a negative electrode current collector; and a coating formation step of exposing the lithium silicate composite particles to a gas phase containing a first element other than non-metallic elements after the supporting step, to form a first coating containing an oxide of the first element on at least a portion of the surface of the lithium silicate composite particles.

14. The method for producing an electrochemical device according to claim 13 , wherein the film forming step is performed by atomic layer deposition.

15. In the preparation step, the lithium silicate composite particles are prepared, at least a part of the surface of which is covered with a carbon coating containing carbon atoms; 15. The method for manufacturing an electrochemical element according to claim 13, wherein in the coating formation step, the first element is introduced into the carbon coating, and a first coating containing an oxide of the first element and the carbon atoms is formed on at least a portion of the surface of the lithium silicate composite particle.

Citation Information

Patent Citations

  • Power storage device, and method for manufacturing the same

    JP2017097999A

  • Negative electrode material for lithium ion secondary battery, negative electrode for lithium ion secondary battery, and lithium ion secondary battery

    JP2019012646A

  • Negative-electrode active material for non-aqueous electrolyte secondary battery, and non-aqueous electrolyte secondary battery

    WO2016121320A1

  • Negative electrode active material for non-aqueous electrolyte secondary cell, negative electrode for non-aqueous electrolyte secondary cell, and non-aqueous electrolyte secondary cell

    WO2016136180A1

  • Negative electrode active material for nonaqueous electrolyte secondary batteries and negative electrode

    WO2017051500A1